The mechanism of pre-trial resolution of financial services consumers’ disputes - Robert Bacho; Bacsó Róbert; Бачо Роберт (II. RFKMF-„RIK-U” Kiadó, 2016)
Abstract. In the article the principle of functioning of the Hungarian Financial Arbitration Board has been disclosed, which was established in 2011. The peculiarities of acceptance and considering of financial services consumers’ complaints has been presented, making a special emphasis on the legislative requirements for the correctness of the complaints submission concerning consumer rights’ violation. It’s generalized that the Financial Arbitration Board does not protect consumers’ rights, but it’s a means for violated rights protection. Statistical analysis of the Board’s activity for the investigated period allows to conclude that it assists to resolve disputes between the parties, which confirms an increasing trend in the proportion of cases settled by amicable agreement between the parties. Introduction of the Hungarian financial arbitration experience in modern Ukrainian realities will help the state’s integration into the European Economic Area by implementing the Commission Recommendation 98/257/EC. In the paper is generalized the necessity for implementation of the mechanism of disputes settlement between consumers and financial institutions, which will strengthen confidence in the financial market and is an additional mechanism for protecting the legal rights of these services’ consumers.

Резюме. В статті розкрито принцип функціонування Фінансової Арбітражної Комісії в Угорщині, що була створена у 2011 році. Відображено особливості прийняття та розгляду скарг споживачів фінансових послуг, особливий акцент роблячи на вимогах законодавства щодо правильності подачі заяв про порушення прав споживача. Узагальнено, що Фінансова Арбітражна Комісія не здійснює захист прав споживачів, а є інструментом захисту порушених прав. Статистичний аналіз діяльності Комісії за досліджуваний період дозволяє робити висновок про її сприяння у врегулюванні спорів між сторонами, про що засвідчує тенденція зростання частки врегульованих справ шляхом укладення мирової угоди сторонами. Впровадження угорського досвіду фінансового арбітражу в сучасних реаліях України сприятиме інтеграції держави у Європейський економічний простір шляхом імплементації Рекомендації Європейської Комісії 98/257/EK. Узагальнення, зроблені в роботі щодо необхідності впровадження даного механізму врегулювання спорів між споживачами на фінансовими установами сприятиме посиленню довіри до фінансового ринку та є додатковим механізмом захисту законних прав споживачів цих послуг.
https://kmf.uz.ua/wp-content/uploads/2017/03/Limes2016_netre.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006463
Keywords: finance; financial services; consumers’ disputes